2019
DOI: 10.3390/ijms20122971
|View full text |Cite
|
Sign up to set email alerts
|

Towards Exploitation of Adaptive Traits for Climate-Resilient Smart Pulses

Abstract: Pulses are the main source of protein and minerals in the vegetarian diet. These are primarily cultivated on marginal lands with few inputs in several resource-poor countries of the world, including several in South Asia. Their cultivation in resource-scarce conditions exposes them to various abiotic and biotic stresses, leading to significant yield losses. Furthermore, climate change due to global warming has increased their vulnerability to emerging new insect pests and abiotic stresses that can become even … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 265 publications
(277 reference statements)
0
40
0
Order By: Relevance
“…The role of these genes for heat tolerance can be studied using CRISPR/Cas9 based targeted gene editing. The mutant population generated after editing of a target gene can be screened for heat tolerance and identified mutants can used in breeding programs for strengthening food security in the future (Kumar, Choudhary, Gupta, & Kumar, 2019). The epigenetic breeding is one of the ways to tackle the problem of heat stress in crop plants (Kumar et al, 2019).…”
Section: Future Ways For Tackling the Problem Of Heat Stressmentioning
confidence: 99%
See 2 more Smart Citations
“…The role of these genes for heat tolerance can be studied using CRISPR/Cas9 based targeted gene editing. The mutant population generated after editing of a target gene can be screened for heat tolerance and identified mutants can used in breeding programs for strengthening food security in the future (Kumar, Choudhary, Gupta, & Kumar, 2019). The epigenetic breeding is one of the ways to tackle the problem of heat stress in crop plants (Kumar et al, 2019).…”
Section: Future Ways For Tackling the Problem Of Heat Stressmentioning
confidence: 99%
“…The mutant population generated after editing of a target gene can be screened for heat tolerance and identified mutants can used in breeding programs for strengthening food security in the future (Kumar, Choudhary, Gupta, & Kumar, 2019). The epigenetic breeding is one of the ways to tackle the problem of heat stress in crop plants (Kumar et al, 2019). Several studies have demonstrated that DNA methylation causing epigenetic variation in crop plants has its role in tolerance to heat stress.…”
Section: Future Ways For Tackling the Problem Of Heat Stressmentioning
confidence: 99%
See 1 more Smart Citation
“…Biotechnological tools like breeding and transgenics have offered strategies for the development of insect‐resistant crops. Moreover, non‐availability of resistant sources and cross incompatibility are major lacunae in breeding for insect resistance in pigeonpea . Hence, scientists worldwide have turned their attention to generate transgenic pigeonpea with better efficacy towards insect herbivory .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, non-availability of resistant sources and cross incompatibility are major lacunae in breeding for insect resistance in pigeonpea. 6,7 Hence, scientists worldwide have turned their attention to generate transgenic pigeonpea with better efficacy towards insect herbivory. [8][9][10][11] Bacillus thuringiensis (Bt) insecticidal proteins (ICPs) that encode a delta endotoxin have proved to be the most suitable and safe alternative to chemical pesticides.…”
Section: Introductionmentioning
confidence: 99%